Kepercayaan dan Keamanan Konsumen terhadap Minat Beli di situs Online (Studi Kasus pengunjung situs Lazada di Jakarta Timur) - Anwar, Resa Nurlela; Afifah, Aulia (Jurnal Manajemen, 2018)
The internet is growing rapidly with an increasing number of regular users. Many people cannot escape the internet in their daily lives and this affects their consumption patterns. The internet has an important role in supporting the development of e-commerce in conducting online transactions. Many online shopping stores have sprung up making people more often make purchasing decisions on a product, and online shopping alone is considered to be much easier and more effective. The purpose of this study was to determine and analyze the influence of consumer trust and security on buying interest on the Lazada site (Survey of visitors to the Lazada site in East Jakarta). The population in this study is Lazada Site Visitors who reside in East Jakarta during January - June 2018 with a total sample of 100 respondents selected using purposive sampling technique. Primary data collection using questionnaires and secondary data collection using literature study. Testing the hypothesis in this study using multiple linear regression analysis with a significance value of a = 10% (0.10). The results showed that trust and security partially and simultaneously have a significant effect on corporate image. Partially, confidence influences asking for a purchase of 9.3% and security has a significant effect on buying interest of 6.3%. The R Square value obtained through testing the determinant coefficient (R2) is what means that advertising affects the company's image by 15.9% and the rest is influenced by other factors not examined in this study.